Everolimus versus sunitinib for patients with metastatic non-clear cell renal cell carcinoma (ASPEN): a multicentre, open-label, randomised phase 2 trial. Issue 3 (March 2016) - Armstrong, Andrew J; Halabi, Susan; Eisen, Tim; Broderick, Samuel; Stadler, Walter M; Jones, Robert J; Garcia, Jorge A; Vaishampayan, Ulka N; Picus, Joel; Hawkins, Robert E; Hainsworth, John D; Kollmannsberger, Christian K; et al.
Summary: Background: Non-clear cell renal cell carcinomas are histologically and genetically diverse kidney cancers with variable prognoses, and their optimum initial treatment is unknown. We aimed to compare the mTOR inhibitor everolimus and the VEGF receptor inhibitor sunitinib in patients with non-clear cell renal cell carcinoma. Methods: We enrolled patients with metastatic papillary, chromophobe, or unclassified non-clear cell renal cell carcinoma with no history of previous systemic treatment. Patients were randomly assigned (1:1) to receive everolimus (10 mg/day) or sunitinib (50 mg/day; 6-week cycles of 4 weeks with treatment followed by 2 weeks without treatment) administered orally until disease progression or unacceptable toxicity. Randomisation was stratified by Memorial Sloan Kettering Cancer Center risk group and papillary histology. The primary endpoint was progression-free survival in the intention-to-treat population using the RECIST 1.1 criteria. Safety was assessed in all patients who were randomly assigned to treatment. This study is registered with ClinicalTrials.gov, number NCT01108445 . Findings: Between Sept 23, 2010, and Oct 28, 2013, 108 patients were randomly assigned to receive either sunitinib (n=51) or everolimus (n=57). As of December, 2014, 87 progression-free survival events had occurred with two remaining active patients, and the trial was closed for the primary analysis. Sunitinib significantly increased progression-free survival compared with everolimus (8·3 months [80% CI 5·8–11·4] vs 5·6 months [5·5–6·0]; hazard ratio 1·41 [80% CI 1·03–1·92]; p=0·16), although heterogeneity of the treatment effect was noted on the basis of histological subtypes and prognostic risk groups. No unexpected toxic effects were reported, and the most common grade 3–4 adverse events were hypertension (12 [24%] of 51 patients in the sunitinib group vs one [2%] of 57 patients in the everolimus group), infection (six [12%] vs four [7%]), diarrhoea (five [10%] vs one [2%]), pneumonitis (none vs five [9%]), stomatitis (none vs five [9%]), and hand-foot syndrome (four [8%] vs none). Interpretation: In patients with metastatic non-clear cell renal cell carcinoma, sunitinib improved progression-free survival compared with everolimus. Future trials of novel agents should account for heterogeneity in disease outcomes based on genetic, histological, and prognostic factors. Funding: Novartis and Pfizer.